Intellectual property rights : development and enforcement in the Arab states of the Gulf / edited by David Price and Alhanoof AlDebasi. - Price, David, 1948-; AlDebasi, Alhanoof (Gulf Research Center book series., 2017)
This volume includes a range of topics addressing aspects of the current status of intellectual property (IP) protection regimes in the Gulf Cooperation Council and its individual member states, and aspiring GCC members Jordan and Yemen. It examines the opportunities and challenges facing the GCC in becoming a real union with common, or at least harmonized, IP laws and regulations, while still allowing flexibility for domestic imperatives and interests. IP is a crucial part of commercial and trade activity which the GCC needs to address as a union to maximize outcomes and benefits for the GCC members collectively and individually. Contributions represent a broad-based and truly international interest in Gulf IP, with authors from Australia, Bahrain, China, Egypt, Indonesia, Jordan, Oman, Qatar, Saudi Arabia, and the United Arab Emirates. The volume provides a catalyst for further deliberation and debate on these above issues and other Gulf-related IP issues, as well as a worthy contribution to the expansion of Gulf studies in the broader context.